If a quadratic function has a vertex at (1, -4) and passes through the point (0, -3), write the equation in factored form.
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To find the equation of the quadratic function in factored form, we start with the vertex form of a quadratic function, which is \(y = a(x - h)^2 + k\). Given the vertex (1, -4), we can express this as \(y = a(x - 1)^2 - 4\). Now, we need to determine the value of \(a\) by using the point (0, -3). Substituting (0, -3) into the equation gives us: \[ -3 = a(0 - 1)^2 - 4 \] \[ -3 = a(1) - 4 \] \[ -3 + 4 = a \] \[ a = 1 \] So the equation becomes \(y = (x - 1)^2 - 4\). Now, to express it in factored form, we can rewrite this as: \[ y = (x - 1 - 2)(x - 1 + 2) = (x - 3)(x + 1) \] Thus, the final equation in factored form is: \[ y = (x - 3)(x + 1) \]